Análise de expressões gênicas da matriz metaloproteinase 3 e 10 no tecido endometrial antes e após embolização arterial de miomas uterinos - Chazan, Franco Loeb [UNIFESP] (2019)
Introduction: Uterine Artery Embolization (UAE), also referred in the medical literature as Uterine Fibroid Embolization (UFE), is a well established therapeutic method for uterine fibroids. However, since there are some concerns about the endometrial integrity after this procedure, there have been several reports questioning this treatment for patients Who suffer from infertility or desire a future pregnancy. These studies believe that UAE could trigger modifications on the molecular biology of the endometrium, such as the gene expression of metalloproteinases during the luteal phase of the menstrual cycle, which analysis needs further investigation. Material and Methods: Twenty women with uterine fibroids undertreatment in the gynecology office of the University of Sao Paulo werere cruited for UAE. Researchers requested magnetic resonance imaging (MRI) and obtained uterine tissue samples from all patients. Two samples were collected from each patient, both between the 20th and the 24th Day of their menstrual cycle, one before the uterine artery embolization and another six months after the procedure. It was performed the extraction of the ribonucleicacid (RNA), the synthesis of the complementary DNA (cDNA) and the real time polymerase chain reaction. The comparative Cq method, also known as 2-ΔΔCT, was used for data analysis, used to calculate the relative quantities (RQ) of gene expression between the samples. Values of p<0.05 were considered statistically significant. Results: Comparing the samples collected before and after the embolization, it was observed a reduction of 9.52 times in the MMP3 expression (p:0,007) and 2,59 times in the MMP10 expression (p:0,22). Conclusions: It was observed a statistically significant reduction of MMP3 gene expression after embolization. No statistically significant variation of MMP 10 gene expression was demonstrated in this study.